Komunikasi Sosial Dalam Media Sosial: (Kajian Etika Komunikasi Remaja di Media Sosial) - Fahreza Sunni, Mohammad; Nashih Ulwan, Muhammad; Arya Ferdian, Dicky; Istofik, Rizal (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
One of the technologies that has become the main pillar in the development of the industrial revolution is the internet. This technology is growing rapidly, has very sophisticated features and makes it easier for humans to access or carry out an activity. Communication that used to be done face-to-face and using manual tools, has now become very easy. Communication does not have to be done face to face or using manual tools such as letters. With computers and smartphones, humans can communicate with anyone without having to meet in person. It is feared that the development of communication technology will shift ethics in communication. Besides having many good benefits, this virtual communication also has a bad impact on humans. Among them forming an individualistic person and can cause a crisis of social communication, especially in the younger generation. The research in this paper uses a qualitative descriptive research type. Descriptive research is intended to collect detailed actual information that describes existing symptoms, identify problems or examine prevailing conditions and practices, make comparisons or evaluations, determine what others have done in facing the same problem and learn from their experiences to determine future and decisions. The results of the study illustrate that how is the ethics of communication among adolescents, especially women, on social media. Both as a communicator and communicant. Communication ethics that are not good make debates that end in insulting each other. If communication is conveyed with sentences that are impolite, rude, and far from moral values, especially when conveyed on social media which are very heterogeneous in nature, it will produce something that is not useful and can even provoke and result in conflict.